1979
DOI: 10.1002/j.1551-8833.1979.tb04423.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing of Home Use Carbon Filters

Abstract: Consumers are buying and installing point-of-use carbon filtration devices at an increasing rate, with little or no guarantee of their advertised efficacy for water quality improvement, and no knowledge of the possible bacterial growth that may occur within the granular activated carbon cartridge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 5 publications
1
11
0
1
Order By: Relevance
“…In this regard, 1t 1s noteworthy that the small carbon filters for home use may cause trouble by Increasing the chloroform content 1n the purified water, for the carbon filters are capable of eliminating or substantially reducing levels of free chlorine residuals, thus causing microorganisms to grow vigorously 1n the carbon beds, which In turn make the chloroform content 1n the effluent Increase markedly over that of the influent, I.e., the tapwater, through biodégradation of chlorinated organic substances adsorbed on the carbon surface. This fact also was verified 1n another study (15).…”
Section: Ho'clsupporting
confidence: 58%
“…In this regard, 1t 1s noteworthy that the small carbon filters for home use may cause trouble by Increasing the chloroform content 1n the purified water, for the carbon filters are capable of eliminating or substantially reducing levels of free chlorine residuals, thus causing microorganisms to grow vigorously 1n the carbon beds, which In turn make the chloroform content 1n the effluent Increase markedly over that of the influent, I.e., the tapwater, through biodégradation of chlorinated organic substances adsorbed on the carbon surface. This fact also was verified 1n another study (15).…”
Section: Ho'clsupporting
confidence: 58%
“…The proliferation of bacteria depends upon the concentration of disinfectant in the distribution system, temperature, season, and the amount of organic matter. Bacterial densities in water after passage through activated carbon containing POU-devices can be expected to increase by one or two logs over the number detected in water supplies (Taylor et al 1979). Wallis et al (1974) observed that bacterial densities increased in devices containing activated carbon after an overnight period of non-use.…”
Section: Introductionmentioning
confidence: 98%
“…Granular activated carbon has an exceptionally high surface area and hence it is frequently used for silver deposition. However, a literature survey indicates that activated carbon filters are susceptible to colonisation (10)(11)(12)(13)(14) and after a certain period of time, shed bacteria into the water. It has also been observed that silver containing activated carbon filters suppress total coliform but not total bacterial growth (15).…”
Section: Introductionmentioning
confidence: 99%